Tourisme pro-pauvre dans les Petites Antilles : éléments de réflexion à partir de l’exemple d’île de Trinidad - Dominique Augier (Études Caribéennes)
The Republic of Trinidad and Tobago, located in the extreme south of the Lesser Antilles, is an exception in the Caribbean region. Indeed, unlike other Caribbean islands, the economy of Trinidad and Tobago depends almost exclusively on industrial and gas sector, while tourism and agriculture involved a small share of gross domestic product of the country.Taking advantage of a favorable international context, Trinidad known for two decades continued economic growth that allows it to display high social indices, but its economy keeps the characteristics of a Small State Islander Developing and faces problems of unemployment and poverty. It’s in this context that the government has initiated a policy of economic diversification identifying several areas of activity, including tourism, likely to reduce poverty. The objective of this study is to analyze the impacts and limitations of pro-poor tourism actions in a small island state through an experiment conducted in the village of Matura in the Northeast of Trinidad.